2022
DOI: 10.1212/nxi.0000000000200020
|View full text |Cite
|
Sign up to set email alerts
|

Myelin Oligodendrocyte Glycoprotein Antibody-Associated Disease Presenting as Intracranial Hypertension

Abstract: The production of autoantibodies against myelin oligodendrocyte glycoprotein (MOG) can cause a spectrum of autoimmune disorders, including optic neuritis, transverse myelitis, brainstem encephalitis, and acute disseminated encephalomyelitis. In this study, we present the case of a 19-year-old woman with an unusual clinical presentation of intracranial hypertension (IH) and bilateral papilledema. The patient presented with symptoms of increased intracranial pressure, which followed a relapsing, remitting course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Signaling pathways include signaling by GPCR [56] and extracellular matrix organization [57] were responsible for advancement of HD. Research has shown that CBLN2 [58], MOG (myelin oligodendrocyte glycoprotein) [59], ROS1 [60], LGR6 [61], GJA5 [62], SUCNR1 [63], REN (renin) [64], VEGFC (vascular endothelial growth factor C) [65], TLR2 [66], FGF12 [67], WT1 [68], SLC22A3 [69], CSRP3 [70], PAPPA2 [71], ACAN (aggrecan) [72], SHH (sonic hedgehog signaling molecule) [73], PDC (phosducin) [74], AGTR1 [75], XDH (xanthine dehydrogenase) [76], P2RX7 [77], NTSR1 [78], SIRT2 [79], RBP4 [80], BMP2 [81], ERBB3 [82], HAS2 [83], CDH13 [84], CSMD1 [85], NR3C2 [86], EPAS1 [87], TRPC6 [88], MMP3 [89], ERAP2 [90], HLA-DRB1 [91], CD74 [92], VWF (von Willebrand factor) [93], MTTP (microsomal triglyceride transfer protein) [494], ANGPT2 [184], AKR1C3 [495], NEDD4L [496], CASP1 [497], LDB2 [498], CHRNA5 [499], CCND2 [500], BRCA2 [97], ZBTB20 [501], EFNB2 [502], CYP7B1 [503], DCLK1 [504], RBM20 [505], PLCE1 [197], protein) [94], NEDD4L [95], CASP1 [96], BRCA2 [97], EFNB2 [98], PLCE1 [99], EGFR (epidermal growth factor receptor) [100], ABCA1 [101], CRHR2 [102], RND3 [103], COMT (catechol-O-methyltransferase) [104] and SMAD9 [105] plays an important role in the pathogenesis of hypertension. Studies have revealed that NEUROD4 [106], SOX10 [107], MOG (myelin oligodendrocyte glycoprotein) [108], NR5A2 [109], GLRA3 [110], FA2H [111], SERPINA […”
Section: Discussionmentioning
confidence: 99%
“…Signaling pathways include signaling by GPCR [56] and extracellular matrix organization [57] were responsible for advancement of HD. Research has shown that CBLN2 [58], MOG (myelin oligodendrocyte glycoprotein) [59], ROS1 [60], LGR6 [61], GJA5 [62], SUCNR1 [63], REN (renin) [64], VEGFC (vascular endothelial growth factor C) [65], TLR2 [66], FGF12 [67], WT1 [68], SLC22A3 [69], CSRP3 [70], PAPPA2 [71], ACAN (aggrecan) [72], SHH (sonic hedgehog signaling molecule) [73], PDC (phosducin) [74], AGTR1 [75], XDH (xanthine dehydrogenase) [76], P2RX7 [77], NTSR1 [78], SIRT2 [79], RBP4 [80], BMP2 [81], ERBB3 [82], HAS2 [83], CDH13 [84], CSMD1 [85], NR3C2 [86], EPAS1 [87], TRPC6 [88], MMP3 [89], ERAP2 [90], HLA-DRB1 [91], CD74 [92], VWF (von Willebrand factor) [93], MTTP (microsomal triglyceride transfer protein) [494], ANGPT2 [184], AKR1C3 [495], NEDD4L [496], CASP1 [497], LDB2 [498], CHRNA5 [499], CCND2 [500], BRCA2 [97], ZBTB20 [501], EFNB2 [502], CYP7B1 [503], DCLK1 [504], RBM20 [505], PLCE1 [197], protein) [94], NEDD4L [95], CASP1 [96], BRCA2 [97], EFNB2 [98], PLCE1 [99], EGFR (epidermal growth factor receptor) [100], ABCA1 [101], CRHR2 [102], RND3 [103], COMT (catechol-O-methyltransferase) [104] and SMAD9 [105] plays an important role in the pathogenesis of hypertension. Studies have revealed that NEUROD4 [106], SOX10 [107], MOG (myelin oligodendrocyte glycoprotein) [108], NR5A2 [109], GLRA3 [110], FA2H [111], SERPINA […”
Section: Discussionmentioning
confidence: 99%
“…Increased cerebrospinal fluid (CSF) in the inflammatory context is more commonly associated with manifestations such as acute disseminated encephalomyelitis or meningoencephalitis [15]. One previously reported potential cause of increased CSF production in MOGAD without evidence of encephalitis might involve low-grade meningeal inflammation producing increased CSF [15].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically it associated fever, headaches, vomiting and possible meningeal irritation signs [46]. Evaluation of CSF is characterized by pleocytosis and elevated cranial pressure [47]. By definition, the complete work-up for infectious aetiology is negative.…”
Section: Core Clinical Demyelinating Events: Classical Features and R...mentioning
confidence: 99%